Fermented rice bran prevents atopic dermatitis in DNCB-treated NC/Nga mice - Saba, Evelyn (J Biomed Res, 2016)
The fermentation of natural plants has a favorable effect on the functional and biological activities of living systems. These include anti-oxidative, anti-inflammatory, and anti-platelet aggregation activities. This is attributed to the chemical conversion of the parent plants to functional constituents, which show more potent biological activity. In our study, rice bran along with oriental medicinal plants (Angelicae gigantis, Cnidium officinale, Artemisia princeps, and Camellia sinensis) was fermented by Lactobacillus rhamnosus and Pichia deserticola (FRBE). We evaluated the effects of oral administration of FRBE on atopic dermatitis in 1-chloro-2,4-dinitrobenzene (DNCB)-treated NC/Nga mice. FRBE significantly ameliorated the macroscopic and microscopic appearance of skin lesions in DNCB-induced atopic dermatitis and reduced levels of serum immunoglobulin E and the differential white blood cell count. In addition, it reduced skin thickness compared to that of atopic dermatitis-affected skin. FRBE treatment also reduced mast cell incorporation in skin lesions of atopic dermatitis. The total cell number in dorsal skin tissue and the axillary lymph node increased following DNCB application, and this was normalized by FRBE treatment. Moreover, it decreased the levels of CD8(+) helper T cells and Gr-1(+)/CD11b(+) B cells in peripheral blood mononuclear cells and skin lesions in DNCB-induced atopic dermatitis. Using real-time polymerase chain reaction analysis, we demonstrated that FRBE significantly inhibited mRNA expression of cytokines (e.g., interleukin-5 and interleukin-13) and cyclooxygenase-2 in AD skin lesions. These results suggest that FRBE could be a valuable herbal remedy for the treatment of atopic dermatitis.